ANALISIS RANTAI PASOKAN (SUPPLAY CHAIN) PADA CV BIOJANNA NUSANTARA KARANGANYAR - Laili, Umi Mufidatul; Riani, Asri Laksmi (Jurnal Pendidikan Insan Mandiri, 2015)
The aims of this study are; 1. To obtain forecasting demand according to customer needs, 2. To get the lowest production costs in the design of the CV Biojanna Nusantara, 3. To get the lowest inventory cost on CV Biojanna Nusantara, 4. To get the right transport models in CV Biojanna Nusantara, 5. To generate the application of supply chain management in CV Biojanna Nusantara.This study uses quantitative methods to the modeling system. data collection techniques of observation, interviews, and documents. The data analysis technique used is demand forecasting, aggregate planning, EOQ, transportation, and supply chain management. The results showed demand forecast for the period of 2015 as many as 444 685 bottles, raw materials inventory management requires a fee of Rp 12,371,327,650, the results of Rp 96,784,275 aggregate planning, the management of inventories of finished products amounted to USD 69 140, and the results of the calculation of the transport of Rp 1,017. 053 450. The total cost to run the flow of supply chain management of Rp 13,485,234,515. After compared with the previously applicable calculation will result in a fee of Rp 13,803,224,736 be obtained savings of Rp 317 990 221. The results of this study demonstrate the application of supply chain management can provide cost and time efficien cy, and to improve services to the consumers better, so companies gain higher profits.Keywords: supply chain management, Industry of traditional medicine